Self-assembled peptido-nanomicelles as an engineered formulation for synergy-enhanced combinational SDT, PDT and chemotherapy to nasopharyngeal carcinoma. Issue 69 (5th August 2019) - Liu, Zhe; Wang, Doudou; Li, Jiaping; Jiang, Yan
Abstract : Peptido-nanomicelles as an engineered formulation for SDT, PDT and chemotherapy to noninvasive treatment to nasopharyngeal carcinoma. Abstract : A formulation of self-assembled peptido-nanomicelles has been developed for a combinational treatment of SDT, PDT and chemotherapy to nasopharyngeal carcinoma. In vitro cellular tests and in vivo mice therapy proved effective for targeted tumor growth inhibition. These merits provided a novel approach to non-invasive cancer treatments.